Investigation and modeling the austenitization kinetics of steels with complex microstructure under continuous heating - Vasilyev, A.A.; Sokolov, D.F.; Sokolov, S.F.; Rudskoy, A.I. (Peter the Great St.Petersburg Polytechnic University, 2019)
An experimental investigation of the austenitization under continuous heating of various microstructures of 8 industrial steel grades with wide range of chemical compositions was carried out. A quantitative mathematical model describing the austenitization kinetics of the steels with complex microstructure and predicting austenite grain size in dependence on the chemical composition, volume fractions of structural components (ferrite, pearlite, bainite, martensite), ferrite grain size and heating rate, was developed. Values of the model empirical parameters were defined basing on the obtained data on kinetics of austenitization, as well as on the measured final austenite grain size. All experiments were performed using the Pocket Jaw unit of the Gleeble 3800 complex. The kinetics of austenitization and the austenite grain size predicted by the developed model are in good agreement with experimental data.